2019
DOI: 10.1080/13674676.2019.1601171
|View full text |Cite
|
Sign up to set email alerts
|

Positive aspects of voice-hearing: a qualitative metasynthesis

Abstract: Voice-hearing occurs in clinical and non-clinical samples, and the role of spiritual and cultural frameworks of understanding for percipients has received increased attention. This review aimed to identify and synthesise the existing qualitative literature relating to positive aspects of voice-hearing experiences, and to make recommendations based on these findings for clinical practice and future research. Qualitative papers that included positive aspects of voice-hearing were identified by undertaking a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Crucially, voices are viewed as social communicative acts (Bell, Mills, Modinos, & Wilkinson, 2017) rooted in relational patterns, beliefs about the self and others (Garety, Bebbington, Fowler, Freeman, & Kuipers, 2007; Morrison, 2001), and interpersonal trauma (Read, van Os, Morrison, & Ross, 2005). Submissive behaviour, a common response to perceived voice threats, maintains distress and a sense of entrapment (Birchwood, Meaden, Trower, Gilbert, & Plaistow, 2000), but, similar to other abusive relationships, voice‐hearers commonly report ambivalence about these relational experiences, including a sense of closeness and companionship (Valavanis, Thompson, & Murray, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, voices are viewed as social communicative acts (Bell, Mills, Modinos, & Wilkinson, 2017) rooted in relational patterns, beliefs about the self and others (Garety, Bebbington, Fowler, Freeman, & Kuipers, 2007; Morrison, 2001), and interpersonal trauma (Read, van Os, Morrison, & Ross, 2005). Submissive behaviour, a common response to perceived voice threats, maintains distress and a sense of entrapment (Birchwood, Meaden, Trower, Gilbert, & Plaistow, 2000), but, similar to other abusive relationships, voice‐hearers commonly report ambivalence about these relational experiences, including a sense of closeness and companionship (Valavanis, Thompson, & Murray, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that, for many, cumulative exposure to multiple trauma subtypes (particularly including physical and sexual trauma) transforms these "protective" voices into more negative, malevolent voices over time. Whilst this is speculative, this hypothesis warrants further exploration, particularly in context of the significance of positive, supportive voice-hearing experiences that are commonly reported in the hearing voices community (Valavanis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In psychological and psychiatric disciplines, hearing voices and related phenomena have been described for a long time mostly as a prodromal stage and as a symptom of psychosis. During the last few decades, the scientific community has been particularly interested in the phenomenon of hearing voices, considering it a normal phenomenon [1][2][3][4][5]; numerous studies have shown that hearing voices is not necessarily something pathologic but that it can actually be functional for the person who experiences it [6].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from this premise, scientific studies began to be interested in those who experience this phenomenon in positive ways, exploring the benefits that can be derived from this condition, which can be defined as a specific cognitive function [10,14,15] or rather called a "capacity" [16]. Among the positive aspects identified, we can mention the function of the voices as a source of encouragement and a way to avert feelings of loneliness [1], encourage personal growth [17], and provide support in critical moments [5]. The role of factors that contribute to making the phenomenon of hearing voices a positive experience for the person has been explored; for example, the frequency of the voices, their content, and coping strategies are important [18], but of particular importance is the quality of the relation between the person and their voices, in addition to their beliefs about it [19].…”
Section: Introductionmentioning
confidence: 99%